Sagot :
Answer:
B
Step-by-step explanation:
-3 : -4 = a : 2
-4(a) = -3(2)
a = -6/-4
a = 3/2
SOLUTION
First find the value of the constant term
[tex] \tt{a = kb} \\ \tt-3 = k(-4) \\ \tt\frac{ - 3}{ - 4} = k \\ \ \tt\frac{3}{4} = k[/tex]
Then, Substituting again the values to get the value of a
[tex] \tt{a = kb} \\ \tt{a} = \tt\frac{3}{4} (2) \\ \tt a = \frac{3}{2} [/tex]
ANSWER
[tex] \large\tt{ \blue{OPTION \: B} \: (3/2)}[/tex]
[tex] \overbrace{ \underbrace{ \tt{} \purple{ \: \: Stay \: safe \: and \: God \: bless \: you! \: \: }}}[/tex]